Nature in common? : environmental ethics and the contested foundations of environmental policy - Minteer, Ben A., 1969- (Temple University Press, 2009)
A groundbreaking contribution to a central debate in environmentalism.
Keywords: Human ecology -- Philosophy.; Environmentalism -- Philosophy.; Environmentalism -- Moral and ethical aspects.; Environmental ethics.; Écologie humaine -- Philosophie.; Environnementalisme -- Philosophie.; Environnementalisme -- Aspect moral.; Éthique de l'environnement.; PHILOSOPHY -- Ethics & Moral Philosophy.; PHILOSOPHY -- General.; Environmental ethics; Environmentalism -- Philosophy; Human ecology -- Philosophy; Umweltethik; Aufsatzsammlung.